Educational inequality across quantiles: Investigating the role of economic determinants - Tunç, Ahmet (IGI Global, 2023)
This study aims to investigate the quantile effects of various economic determinants on educational inequality. To this aim, the authors utilize the method of moments quantile regression (MMQR) in this empirical investigation, focusing on two separate panels of data; one including countries classified as developed (MSCI-D) and the other including developing (MSCI-E) countries by the MSCI standard index. Results reveal that both per capita income and female unemployment are important tools in reducing educational inequality for all country panels. Government expenditures on education, while reducing educational inequality in developed countries, exhibit no significant effect in developing countries. Similarly, income inequality positively affects educational inequality in developing countries, whereas it does not exert any significant effect in developed countries. These findings provide valuable insights, emphasizing the importance of considering the specific economic conditions within countries when designing policies, and interventions aimed at reducing educational inequality. © 2023, IGI Global. All rights reserved.